2022
DOI: 10.1177/17455057221109362
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the development of new-onset and persistent postpartum preeclampsia: A case–control study in Ghana

Abstract: Background: Postpartum preeclampsia has been implicated in increasing hospital re-admissions, maternal morbidity, and mortality worldwide. The knowledge of the risk factors of postpartum preeclampsia would be helpful in formulating strategies to aid in the prevention, early diagnosis, and timely treatment of this disorder. Thus, this study aimed to identify the risk factors associated with the development of new-onset postpartum preeclampsia and persistent postpartum preeclampsia in the Ghanaian setting. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 34 publications
4
7
0
Order By: Relevance
“…The association between family history of hypertension and the incidence of preeclampsia has been reported by previous studies [26–28]. Preeclampsia persists after delivery discharge in women with a family history of hypertension [29]. Our findings agree with this previous study and go further to show that such patients are likely to be readmitted.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The association between family history of hypertension and the incidence of preeclampsia has been reported by previous studies [26–28]. Preeclampsia persists after delivery discharge in women with a family history of hypertension [29]. Our findings agree with this previous study and go further to show that such patients are likely to be readmitted.…”
Section: Discussionsupporting
confidence: 93%
“…One study reported no significant association between parity groups and readmission [21]. Another study showed no association between the persistence of preeclampsia after delivery and parity groups [29]. These conflicting reports may be due to the small sample size of this study or external factors such as the quality of prenatal care received and dietary and lifestyle practices, which were not assessed in this study.…”
Section: Discussionmentioning
confidence: 86%
“…Our study also revealed that poor previous obstetric outcome like cesarean section (CS) had relationship with PE in consonance with a previous study which stated that regardless of parity or gestational age, cesarean deliveries were more common in preeclamptic women who had labor induction than in non-preeclamptics [25], [26]. Compared to the normotensives, those with family history of hypertension had higher risk of developing PE in line with a similar study done in Kumasi, Ghana [25]. Our study did not nd signi cant relationship between parity, gravidity, stillbirth, miscarriages and PE though many studies have linked these factors to the onset of PE.…”
Section: Discussionsupporting
confidence: 91%
“…Physical inactivity and other risk factors were investigated by Fondjo et al 29 in the pursuit of understanding postpartum preeclampsia. Postpartum preeclampsia poses significant risks globally, including hospital readmissions and maternal complications.…”
Section: Prenatal Care and Maternal And Neonatal Health Outcomesmentioning
confidence: 99%